2012
DOI: 10.1371/journal.pone.0040830
|View full text |Cite
|
Sign up to set email alerts
|

Cord Blood Leptin Levels of Healthy Neonates Are Associated with IFN-γ Production by Cord Blood T-Cells

Abstract: Leptin is a hormone synthesized by adipocytes and other tissues, including the placenta, and it regulates food intake and energy expenditure, reproductive and immune functions. To investigate the role of leptin in neonatal immunity, we measured serum leptin and cytokine (IFN-γ, TNF-α, IL-2, IL-4, IL-10, IL-12) levels in the cord blood (cb) of 510 healthy neonates, 14 small for gestational age (SGA), 312 appropriately grown for gestational age (AGA) and 184 large for gestational age (LGA). Median serum leptin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 67 publications
(72 reference statements)
1
8
0
Order By: Relevance
“…Enhanced circulating leptin in obese women was associated with higher leptin and monocyte concentrations in cord blood. In addition to its potential role in newborn adiposity ( 64 , 67 ), growing evidence has linked leptin with the maturation of the hypothalamus ( 68 ) and the fetal and neonatal immune system ( 69 ), leading to impaired immune responses ( 59 ). As part of the PREOBE follow-up, further studies are exploring potential long-term implications of obesity and diabetes in offspring neurodevelopment through functional measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced circulating leptin in obese women was associated with higher leptin and monocyte concentrations in cord blood. In addition to its potential role in newborn adiposity ( 64 , 67 ), growing evidence has linked leptin with the maturation of the hypothalamus ( 68 ) and the fetal and neonatal immune system ( 69 ), leading to impaired immune responses ( 59 ). As part of the PREOBE follow-up, further studies are exploring potential long-term implications of obesity and diabetes in offspring neurodevelopment through functional measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, energy restriction decreases serum concentrations of IgG and IgA in overweight women . However, it has also been reported that the appetite‐regulating hormone leptin may modulate different aspects of adaptive immunity .…”
Section: Discussionmentioning
confidence: 99%
“…Although, the weight parameters for our cohort were largely in the normal range with the majority of children having normal birth weight and only 3.2% reporting low birth weight and 8.4% high birth weight, a high percentage had elevated leptin levels. The mean cord blood leptin in our cohort was 23.0 ± 18.4 ng/mL while 25.4% of the cohort had high leptin defined as leptin levels >90th percentile for neonates (>28 ng/mL) from the study by [14]. The mean leptin levels in our cohort were much higher (more than 50%) than the 15.7 ng/mL reported for Taiwanese infants [15] and also higher than the 13.97 ng/mL for large for gestational age infants in a US sample [16].…”
Section: Discussionmentioning
confidence: 99%